Spectroscopic properties of Yb3+ doped PbO-Bi2O3-Ga2O3 glasses for IR laser applications - Kassab, LRP; Fukumoto, M. E.; Cacho, VDD; Wetter, N. U.; Morimoto, N. I. (Elsevier B.V., 2005)
PbO-Bi2O3-Ga2O3 glasses doped with different concentrations of Yb3+ are presented. The spectroscopic properties and laser parameters are calculated and a comparison between different results obtained when calculating the Yb3+ emission cross-section with the reciprocity method and with the Fuchtbauer-Ladenburg formula is presented. The behavior of the near-infrared luminescence is described theoretically by a rate equation and compared with the experimental results. This host doped with Yb3+ is a promising material for laser action at 1019 nm, with properties similar to other known glasses used as active laser media; the emission cross-section of 1.1 x 10(-20) cm(2), the high absorption cross-section (of 2.0 x 10(-20) cm(2)) and a minimum pump intensity of 2.4 kW/cm(2) are interesting properties for short pulse generation. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: glasses; ytterbium; fluorescence